The Impact Of Edc's Marketing, Service, And Infrastructure Strategies On The Growth Of Savings Deposits At Bank Rakyat Indonesia Surabaya Pahlawan Branch - Wike Dwi Septianingrum; Fitri Ismiyanti (Jurnal Indonesia Sosial Teknologi, 2023)
Banking strategy requires fast and instant service to provide "excellent service" to customers. One of the marketing methods used as technology development in the banking industry, for example at PT Bank Rakyat Indonesia Surabaya Pahlawan Branch, is a marketing approach using Electronic Data Capture (EDC). This tool has the benefit of growing third-party funds, especially savings funds and fee-based income obtained from every transaction carried out on the EDC machine. In addition, there are efforts to increase the amount of savings, especially low-cost funds (savings) in a way that is more dominant to the number of third-party funds, to reduce the cost of funds and is expected to generate an increase in the value of net interest margin (NIM) despite the current tight bank liquidity. The purpose of this study is to see the influence of Marketing Strategy, Service Strategy, and Electronic Data Capture (EDC) Infrastructure on the Growth of Savings Deposits at PT Bank Rakyat Indonesia Surabaya Pahlawan Branch. This study used multiple linear regression with the help of the SPSS version 23 application to help with data processing. The results showed that the variables Marketing Strategy (X1), Service Strategy (X2), and Electronic Data Capture Infrastructure (X3) had a positive and significant influence on the increase in Savings Deposit Growth (Y) by the regression coefficient.